Effects of subject pool culture and institutional environment on corruption: Experimental evidence from Albania - Harri, Ardian; Zhllima, Edvin; Imami, Drini; Coatney, Kalyn T. (Economic systems, 2020)
This research uses experimental methods to investigate whether subject pool culture and institutional environment have an effect on participants’ corrupt behavior in the laboratory. While we find that subject pool culture does not affect the overall magnitude of corruption of laboratory participants, it does affect the likelihood of corruption and its distribution. Additionally, we find that the effect on corrupt behavior differs with the framing of the experiment’s instructions. Interestingly, in the context of a weak rule of law and high levels of corruption, loaded negative instructions positively affect corrupt behavior of firms and public officials. Previous research in the context of a country exhibiting a strong rule of law and low levels of corruption finds no framing effects. We also find that increasing the probability of detection significantly reduces corruption as measured by the amount of the bribes offered/accepted and the probability of offering/accepting a bribe. Finally, we find that individual risk preferences negatively affect the level of corrupt behavior.